Chromosome-level genome assembly of a stored-product psocid, Liposcelis tricolor (Psocodea: Liposcelididae) - Shi-Die Jiang; Yu-Ang Chen; Sheng-Yuan Sun; Guy Smagghe; Jin-Jun Wang; Dan-Dan Wei (Scientific Data)
Abstract Liposcelis tricolor (Psocoptera: Liposcelididae) is a significant pest affecting stored products globally. However, due to the lack of a detailed genomic reference, the mechanisms of sex determination, stress resistance, and potential control methods for this booklouse remain poorly understood. In this study, the chromosome-level genome of L. tricolor was assembled by employing Illumina, Nanopore, and Hi-C sequencing technologies. The final genome size was determined to be 229.33 Mb, anchored to 9 pseudo-chromosomes. BUSCO analysis showed that 99.2% of complete BUSCOs were identified, suggesting the high completeness of the genome. A total of 91.49 Mb of repetitive sequences, accounting for 38.84% of the total genome, were annotated, and 15,647 protein-coding genes were predicted, with 88.17% functionally annotated. Additionally, we identified 25 typical sex-determining genes based on the genomic data. This high-quality genome assembly provides a crucial foundation for advancing our comprehension of the molecular biology, genetics, and potential control strategies for psocid L. tricolor.